2008
DOI: 10.1182/blood-2008-04-149641
|View full text |Cite
|
Sign up to set email alerts
|

E-selectin receptors on human leukocytes

Abstract: Selectins on activated vascular endothelium mediate inflammation by binding to complementary carbohydrates on circulating neutrophils. The human neutrophil receptor for E-selectin has not been established. We report here that sialylated glycosphingolipids with 5 Nacetyllactosamine (LacNAc, Gal␤1-4Glc-NAc␤1-3) repeats and 2 to 3 fucose residues are major functional E-selectin receptors on human neutrophils. Glycolipids were extracted from 10 10 normal peripheral blood human neutrophils. Individual glycolipid sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 66 publications
1
121
0
1
Order By: Relevance
“…Attempts were made to inhibit Ply cytotoxicity against human PMNs and PBMCs with sLeX, but no inhibition was observed. The failure of sLeX to inhibit Ply cytotoxicity against these cells may be due to the overload of sLeXcontaining glycoproteins and glycolipids on the surface of human PMNs, particularly neutrophils (39,40), or to the presence of alternative receptors for Ply on human leukocytes. However, sLeX did inhibit cytotoxicity of Ply for A549 (human alveolar) cells, suggesting that this glycan present on glycolipids and/or glycoproteins may serve as a receptor for Ply on cell types other than RBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts were made to inhibit Ply cytotoxicity against human PMNs and PBMCs with sLeX, but no inhibition was observed. The failure of sLeX to inhibit Ply cytotoxicity against these cells may be due to the overload of sLeXcontaining glycoproteins and glycolipids on the surface of human PMNs, particularly neutrophils (39,40), or to the presence of alternative receptors for Ply on human leukocytes. However, sLeX did inhibit cytotoxicity of Ply for A549 (human alveolar) cells, suggesting that this glycan present on glycolipids and/or glycoproteins may serve as a receptor for Ply on cell types other than RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…L-selectin is found on most leukocytes and binds to glycoproteins carrying an O-linked sLeX with a sulfate on the 6-hydroxyl of the GlcNAc residue, such as glycosylation-dependent cell adhesion molecule 1 (38). E-selectin is found on activated endothelium and appears to bind sLeX on sialylated glycosphingolipids on human neutrophils (39). It has also been reported that Mac1 (CD11b/ CD18) of human neutrophils, a major membrane protein decorated with sLeX, binds to E-selectin and that the sLeX moieties are critical for this interaction (40).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, E-selectin ligands on mouse but not human neutrophils are pronase-sensitive (7,8). 3 In this regard, Nimrichter et al (47) suggest that a relatively minor monosialylated, polyfucosylated glycolipid with poly-lactosamine units NeuAc␣␣2,3Gal␤1,4GlcNAc␤1,3[Gal␤1,4 (Fuc␣1,3)GlcNAc␤1,3] 2 [Gal␤1,4GlcNAc␤1,3] 2 Gal␤1,4Glc␤Cer…”
Section: Fut7mentioning
confidence: 99%
“…These findings suggest that G-CSF stimulates de novo expression of HECA-452-reactive moieties predominantly on N-glycans. The residual HECA-452 determinants displayed in the presence of DMJ likely reflect the native contribution(s) of sialofucosylated O-linked glycans found on both glycoproteins and glycolipids (18,19).…”
Section: N-glycan Processing Is Required For G-csf-induced Sialofucosmentioning
confidence: 99%